Development of a Digital Attendance System Using the Appsheet Application with GPS and Biometric Verification - Darojah, Darojah; Nurkolis, Nurkolis; Ariyanto, Lilik (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to develop a digital attendance application based on AppSheet at SMPN 2 Satu Atap Sluke, Sluke District, Rembang Regency, with a focus on measuring the validity, practicality, and excellence of the product. The application is designed as an innovative solution to replace the manual attendance system that has been used so far, which often poses challenges related to data accuracy and student discipline. The research method employed is Research and Development (R&D) using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was carried out through interviews, questionnaires, observations, and document analysis. The collected data were analyzed using descriptive techniques and hypothesis testing through expert validation, product practicality tests, one-sample t-tests, and simple linear regression tests. The results show that the digital attendance application based on AppSheet was declared highly valid with a score of 98% and an average of 92.31%, categorized as “Very Good.” In addition, the application proved to be practical, superior compared to manual attendance, and effective in improving student attendance discipline, although statistically the effect was not significant. In conclusion, this application meets the quality criteria in terms of content, appearance, and functionality, making it feasible for use. The novelty of this study lies in the utilization of AppSheet with the integration of GPS and biometric technologies, which have not previously been applied in school attendance systems.